STYLISTIC ANALYSIS OF PERFUME ADVERTISING LANGUAGE: REPRESENTATION OF GENDER ISSUES - Ida Cahyani (Language and Literature Faculty, Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2023)
This article describes the stylistics analysis of language in perfume advertisement which correlates to gender issue. This topic was chosen due to the critical view on language and gender issue especially in advertisement which promotes the idea of masculinity and femininity represented by the name of the product, their taglines and the description of the product. This research aims at describing the stylistic features of the product name, the tagline and the description in the perfume advertisement. The method of research includes the method of collecting data which is from Oriflame advertisement in the form of a catalog and the method of data analysis which applies Mills' feminist stylistics (1998). The result shows that the naming of perfume represents the gender issue such as the representation of femininity in the perfume for women and masculinity in the perfume for men. Besides, the tagline marks femininity and masculinity in several directions correlate to women and men's nature. Meanwhile, the description of the product contains a lot of style, namely hyperbole, metaphor and personification to beautify the language of the advertisement as well as to promote gender issues to enlarge the target market of the product being promoted.